PENGARUH PENERAPAN METODE BERVARIASI TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADIST - Lilik Masruroh; Wachyudi Achmad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2019)
Along with advances in technology at this time learning continues to experience development where basically learning is an effort to help students to grow and develop in education. A teacher who pays attention to situations, conditions of tolerance, views and reach of students is encouraging or causing variations in teaching. Which one of them is by combining or varying the teaching methods so that in the teaching process the teacher is not fixated on just one method and this aims so that students do not feel bored in the learning process. Departing from the above background, the researcher took the problem of implementing varied methods in increasing student achievement in MTs AL-MUSTOFA Bangil and the effect of variation methods in teaching the Al-Qur'an's Hadith to increasing student achievement. This research is a type of quantitative research. This is done because in accordance with the survey conducted requires sharpness and accuracy in observing the problem under study. In addition, in collecting data the author uses the method of observation, questionnaires, interviews and documentation. The method is a tool in teaching, its use must be done as much as possible in the teaching and learning process, and the results of this study are: 1) The implementation of the method varies in increasing student learning achievement. 2) The effect of varying teaching methods on student achievement is very positive influence for students and can be categorized quite well in meeting learning objectives with the evidence that and the results obtained are rxy> rcritic, the null hypothesis (Ho) rejected and work hypothesis (Ha) accepted.